2013
DOI: 10.1152/ajpregu.00558.2012
|View full text |Cite
|
Sign up to set email alerts
|

Bladder outlet obstruction triggers neural plasticity in sensory pathways and contributes to impaired sensitivity in erectile dysfunction

Abstract: Lower urinary tract symptoms (LUTS) and erectile dysfunction (ED) are common problems in aging males worldwide. The objective of this work was to evaluate the effects of bladder neck nerve damage induced by partial bladder outlet obstruction (PBOO) on sensory innervation of the corpus cavernosum (CC) and CC smooth muscle (CCSM) using a rat model of PBOO induced by a partial ligation of the bladder neck. Retrograde labeling technique was used to label dorsal root ganglion (DRG) neurons that innervate the urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 62 publications
7
9
0
Order By: Relevance
“…Six weeks PBOO caused a more pronounced detrusor hypertrophy than obstruction for 3 weeks. This supports the recent data by Malykhina et al, 14 where partial obstruction of the bladder neck for 2 weeks induced a significant hypertrophy (2.5-fold increase) of the urinary bladder. In this study, the average bladder weight was 124 mg in sham-operated rats and 287 mg in animals with PBOO (132% increase).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Six weeks PBOO caused a more pronounced detrusor hypertrophy than obstruction for 3 weeks. This supports the recent data by Malykhina et al, 14 where partial obstruction of the bladder neck for 2 weeks induced a significant hypertrophy (2.5-fold increase) of the urinary bladder. In this study, the average bladder weight was 124 mg in sham-operated rats and 287 mg in animals with PBOO (132% increase).…”
Section: Discussionsupporting
confidence: 92%
“…This supports the recent data by Malykhina et al, where partial obstruction of the bladder neck for 2 weeks induced a significant hypertrophy (2.5‐fold increase) of the urinary bladder. In this study, the average bladder weight was 124 mg in sham‐operated rats and 287 mg in animals with PBOO (132% increase) . In another study by Yuan et al, the mean bladder weight was 14 mg for the young group, 37 and 70 mg for the PBOO‐3wk and ‐6wk group, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, some studies demonstrated that the contractile responses of CC strips to Phe were decreased after PBOO . The finding that Phe‐induced contractions of CC is increased in PBOO but restored by silodosin appears harmonious.…”
Section: Discussionmentioning
confidence: 99%